Self-inflicted injury and secondary cerebral abscess in a patient with schizophrenia - Gibaja Reyes, Diashania (2023)
Self-injury is the intentional act of causing harm to oneself, without suicidal purposes. This case report describes a 37-year-old schizophrenic patient, with a history of 20 years, and recent symptoms of irritability, aggressiveness, isolation, self-harm and contamination ideas (“I have a staphylococcus in my head”). For 10 years, he used avariety of objects to manipulate himself, among them a scalpel with which he extirpated part of the calotte, causing a vasogenic edema in the left cortico-fronto-parietal region that produced a right brachio-crural haemiparesis, the reason for his admission. After ruling out a stroke or a brain tumor, he underwent surgery for the removal of a brain abscess; he received several antipsychotic agents with only a partial response that later improved after being switched to paliperidone. In cases like this, it is necessary to conduct a timely screening, diagnosis and treatment in order to avoid a torpid evolution and prognosis in schizophrenic patients with long-standing self-inflicted injuries and a history of poor adherence and response to treatment.